2007
DOI: 10.1136/bjo.2007.118497
|View full text |Cite
|
Sign up to set email alerts
|

Association between integrity of foveal photoreceptor layer and visual acuity in branch retinal vein occlusion

Abstract: Aim: To study the correlation between integrity of the photoreceptor layer after resolution of macular oedema (MO) associated with branch retinal vein occlusion (BRVO) and final visual acuity (VA), and to determine prognostic factors for visual outcome. Methods: We retrospectively studied 46 eyes from 46 patients with resolved MO secondary to BRVO, the foveal thickness of which was less than 250 mm at final observation. We assessed the status of the third high reflectance band (HRB) in the fovea using optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 25 publications
6
89
2
5
Order By: Relevance
“…In addition, logMAR BCVA in the IS/OS(À) eye group was significantly worse than that in the IS/OS( þ ) eye group. This supports the hypothesis that the IS/OS line detected by OCT reflects integrity of the photoreceptor layer, and, accordingly, vision of eyes with an ill-defined IS/OS line is poor, as has been shown previously in reports of several other retinal diseases about the relationship between visual acuity and the IS/OS line as seen by OCT, [8][9][10][11][12] and we have now suggested that this may be the case in patients with Behçet's disease. Second, the ratio of men to women in the IS/OSi( þ ) eye group or the IS/OS( þ / þ ) patient group was significantly lower than that in the IS/OS(À) or the IS/OS(À/) patient group.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In addition, logMAR BCVA in the IS/OS(À) eye group was significantly worse than that in the IS/OS( þ ) eye group. This supports the hypothesis that the IS/OS line detected by OCT reflects integrity of the photoreceptor layer, and, accordingly, vision of eyes with an ill-defined IS/OS line is poor, as has been shown previously in reports of several other retinal diseases about the relationship between visual acuity and the IS/OS line as seen by OCT, [8][9][10][11][12] and we have now suggested that this may be the case in patients with Behçet's disease. Second, the ratio of men to women in the IS/OSi( þ ) eye group or the IS/OS( þ / þ ) patient group was significantly lower than that in the IS/OS(À) or the IS/OS(À/) patient group.…”
supporting
confidence: 71%
“…With the use of highresolution and contrast, OCT also allows us to evaluate the junctions between inner and outer segments (IS/OS) of the photoreceptors, which have been reported to have a close relationship with visual function in various conditions, including macular hole, 8,9 branch retinal vein occlusion, 10,11 and retinal detachment. 12 Because drastic changes in macula, for example, macular oedema, retinal haemorrhage, or ischaemia are seen in active phase of Behçet's disease, the status of IS/OS line on OCT in Behçet's eye is attracting a great deal of attention as a possible hallmark of the integrity of the outer photoreceptor layer.…”
Section: Introductionmentioning
confidence: 99%
“…8 Distortion, shortening, or absence of IS/OS may indicate pathologic changes in photoreceptors as shown in RP 16 as well as in macular hole, 20 retinal detachment, 14 retinal vein occlusion, 21 central serous chorioretinopathy, 13,15,22 or multiple evanescent white dot syndrome. 23 Also in our patients, complete disappearance of IS/OS detected by OCT was correlated with decrease in VA, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15]16 On OCT imaging, the HRB is identified as a distinct band just above the highreflectance layer of the retinal pigment epitheliumchoriocapillaris complex, best detected in greyscale mode (Figure 2). 17 The HRB was analysed in the area corresponding to the central 3 mm grid of the ETDRS chart and classified into three groups: intact (group 1), disrupted (group 2), or absent (group 3), depending on …”
Section: Hyper-reflective Band (Hrb)mentioning
confidence: 99%